Circulation of cosmogenic 22Na using the global monitoring network of the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO). (July 2018) - Hoffman, I.; Lewis, B.; Chan, P.
Abstract: Using a recently published global data set of 22 Na and 7 Be from the global monitoring network of the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO), atmospheric circulation and stratosphere-troposphere interactions are examined. Cosmogenic 22 Na has a half-life well-suited to environmental processes with durations from several months to a decade. Combined with corresponding 7 Be observations, these two cosmogenic isotopes form a useful environmental tracer and new radiochronometer to study physical interactions of air masses in the stratosphere and troposphere. Highlights: A database of concentrations of 22 Na and 7 Be was used to study global circulation. A semi-empirical production model and a simple box model were employed. Global atmospheric concentrations of 22 Na were found to behave similarly to 7 Be.